2024
DOI: 10.3390/ma17061298
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties and Drying Shrinkage Performance of Palm Kernel Shell Ash and Rice Husk Ash-Based Geopolymer Concrete

Mohd Na’im Abdullah,
Faizal Mustapha,
Nurul ‘Izzati Yusof
et al.

Abstract: This study aims to develop suitable formulations of geopolymer concrete (GPC) by varying the percentages of the geopolymer with aggregates and evaluating the performances in thermal and mechanical properties of palm kernel shell ash (PKSA)-GPC compared to rice husk ash (RHA)-GPC and ordinary Portland cement concrete (OPCC). Preliminary tests were conducted to select the best mix design ratios before casting the specimens. Then, the performance of the PKSA-GPC, RHA-GPC and OPCC specimens was evaluated based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It has been reported that AASC can reduce CO 2 emissions by 25-80% relative to OPC [11][12][13]. AASC has similar or better mechanical performance and durability than OPC [14][15][16][17]. However, in order to apply AASC to full-scale construction, certain problems, such as low carbonation resistance [18][19][20], alkali-aggregate reaction [21], and shrinkage [22][23][24][25][26][27][28][29][30], must be solved or improved.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that AASC can reduce CO 2 emissions by 25-80% relative to OPC [11][12][13]. AASC has similar or better mechanical performance and durability than OPC [14][15][16][17]. However, in order to apply AASC to full-scale construction, certain problems, such as low carbonation resistance [18][19][20], alkali-aggregate reaction [21], and shrinkage [22][23][24][25][26][27][28][29][30], must be solved or improved.…”
Section: Introductionmentioning
confidence: 99%
“…These cements involve the partial or complete replacement of the PC [5,6] with supplementary cementitious materials (SCM), such as natural pozzolan (volcanic materials), limestone, blast furnace slag, fly ash, calcinated clays and waste glass [7,8]. These alternative cements offer advantages including lower CO 2 emission compared to PC, good mechanical strength, thermal resistance, among others [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%